Dynamic performance of hybrid robot controllers near singularities - Azenha, Abílio (1998)
This paper studies the performance of a variable structure algorithm in the position/force hybrid of robotic manipulators. It is shown that a reformulation of the kinematic position loop using pseudo-inverses improves the system response namely in the neighbourhood of singular points. The robustness and the system dynamics are analyzed in terms of frequency and time responses.